E4F1 silencing inhibits the cell growth through cell‐cycle arrest in malignant transformed cells induced by hydroquinone. Issue 4 (1st December 2018) - Tan, Qiang; Li, Jieyou; Peng, Jianming; Liu, Zhidong; Liu, Jiaxian; Zhang, Haiqiao; Yuan, Qian; Pan, Zhijie; Liu, Linhua
Abstract: Hydroquinone (HQ), one of the most significant metabolic activation products of benzene in an organism, can cause hematological toxicity, such as acute myeloid leukemia. It is a clear carcinogen that can cause changes in the disorder of cell cycle and cell growth. However, its molecular mechanisms remain unclear. E4 transcription factor 1 (E4F1), an important transcription factor, participating in the regulation of cell cycle may be related to the occurrence of tumor. Here, we examined the HQ‐induced malignant transformed TK6 cells (TK6‐HT) to illustrate the role of E4F1 in carcinogenesis. The present study showed that both the expressions of E4F1 messenger RNA and protein increased obviously in TK6‐HT, preliminarily indicating that E4F1 is associated with HQ‐induced carcinogenesis. To further explore the role of E4F1, we established E4F1 silencing TK6‐HT (pLVX‐shE4F1) and its control cells (pLVX‐shNC) using lentiviral short hairpin RNA (shRNA) interference expression plasmid vector pLVX‐shRNA. Flow cytometry and cell counting kit‐8 assay were used to determine the effects of E4F1 silencing on cell cycle and cell growth, respectively. E4F1 silencing inhibited cell growth in TK6‐HT. The results from flow cytometry indicated that the inhibitory effect on cell growth may be the results of the E4F1 silencing–induced accumulation in G2/M compared with TK6‐HT‐shNC. Meanwhile, levels of DNA damage (γ‐H2AX), proteins of Rb and phosphorylated Rb, and reactive oxygen species were increased in TK6‐HT‐shRNA2 cells, which is the critical reason of cell‐cycle arrest. In conclusion, E4F1 silencing inhibits the cell growth through cell‐cycle arrest in malignant transformed cells induced by HQ.